Composite fiber textile fabric and method for manufacturing the same
Patent Information
- Application Number
- CN202411668943.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-11-21
AI Technical Summary
(1)本发明的纺织布料由尼龙、改性涤棉纤维和海岛纤维组成,尼龙和改性涤棉纤维的高强度和耐磨性,使得面料具有更好的耐用性和抗撕裂性,即使在多次洗涤后仍能保持良好的抗菌和自清洁性能,海岛纤维的微细结构和适当的纺织工艺可以使织物具有良好的防水性和透气性,同时提供隔热保暖效果,且海岛纤维的耐磨性和强度较高,可以经受住一定程度的洗涤和使用,保持良好的外观和性能,另外海岛纤维具有天然的抗菌性能,能够有效防止细菌和霉菌的滋生。
Smart Images

Figure CN119593127B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile fabric technology, specifically to a composite fiber textile fabric and its preparation method. Background Technology
[0002] Composite fiber is a type of multi-component fiber, a term used to describe various types of man-made fibers. A composite fiber contains two or more immiscible polymer fibers in its cross-section; it is a physically modified fiber developed in the 1960s. Composite fiber manufacturing technology can produce bicomponent fibers that combine the properties of two polymers. Types include side-by-side, core-sheath, and island-of-the-sea composite fibers, with circular and irregular cross-sections. These fibers possess three-dimensional crimp, high bulk and coverage, good electrical conductivity, antistatic properties, and flame retardancy. Composite fibers require a specially structured composite spinning machine for spinning. They are mainly used in yarn, blankets, wool fabrics, thermal insulation fillings, silk fabrics, non-woven fabrics, medical and hygiene products, and special workwear.
[0003] With the diversification of infectious diseases, enhancing the antibacterial and purifying effects of fabrics is of great significance for improving personal hygiene, reducing disease transmission, extending the lifespan of textiles, and adapting to specific environments. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a composite fiber textile fabric and its preparation method.
[0005] A composite fiber textile fabric, comprising the following components by weight percentage: Nylon: 60~80%; Composite fiber: Balance; The composite fiber is composed of modified polyester-cotton fiber and island fiber in a mass ratio of 1:0.4~0.6.
[0006] Furthermore, the method for preparing the modified polyester-cotton fiber is as follows: Polyester-cotton fibers were immersed in a hydrogel precursor solution at a solid-liquid ratio of 1g:40-60mL. A vacuum was applied to reduce the pressure to 70-75kPa. The hydrogel precursor solution was then heated to 85-95℃ and maintained for 30-40 minutes. The surface of the polyester-cotton fibers was then subjected to corona treatment. The irradiation temperature for the corona treatment was 20-40℃, the voltage was 15-25kV, and the treatment time was 5-15 minutes. The distance between the electrodes of the corona treatment device and the polyester-cotton fibers was 0.5-4.5mm. After the corona treatment, the obtained polyester-cotton fibers were immersed in a 10-20% sodium hydroxide solution at a solid-liquid ratio of 1g:20-30mL. A vacuum was applied again to reduce the pressure to 10-20kPa and maintained for 5-10 minutes. The polyester-cotton fibers were then removed and dried to obtain modified polyester-cotton fibers.
[0007] Explanation: Vacuum conditions help remove air from inside the fibers, allowing the hydrogel precursor solution to penetrate more easily, thus improving permeability. By controlling vacuum and heating conditions, the interfacial bonding between the fibers and the hydrogel precursor solution can be optimized, forming a more uniform and robust composite material. Corona treatment can introduce hydrophilic groups, such as carboxyl and hydroxyl groups, onto the fiber surface. These groups increase the surface energy of the fibers, thereby improving hydrophilicity. Furthermore, corona treatment significantly reduces the electrostatic half-life of the fiber surface, improving antistatic properties. Alkaline solutions can soften the fiber surface, increasing the affinity between the cellulose solution and the polyester-cotton fibers. This helps the cellulose solution to better penetrate and adhere to the fibers, forming a more uniform and stable hydrogel layer on the fiber surface. This contributes to improving the morphology and microstructure of the final composite material.
[0008] Furthermore, the hydrogel precursor solution comprises, by weight, 15-20 parts cellulose solution, 5-10 parts antibacterial agent, 3-5 parts nano zinc oxide, and 8-10 parts octadecyl mercaptan.
[0009] Note: Cellulose solution enhances the mechanical strength and toughness of the fabric, while octadecyl mercaptan, as a surfactant, helps improve the interfacial bonding between the fiber and the hydrogel precursor, further improving the mechanical properties of the composite material. The presence of antibacterial agents and nano-zinc oxide provides the fabric with antibacterial properties. Due to its high specific surface area and photocatalytic activity, nano-zinc oxide can effectively kill bacteria and fungi, enhancing the hygiene and safety of the fabric.
[0010] Furthermore, the antibacterial agent is a silver ion antibacterial agent or a guanidine antibacterial agent, and the particle size of the nano zinc oxide is 40~50nm.
[0011] Note: Silver ion antibacterial agents have high wash resistance and can maintain good antibacterial performance even after multiple washes; guanidine antibacterial agents are compatible with a variety of fabric materials and are suitable for different textile processing techniques.
[0012] A method for preparing a composite fiber textile fabric as described in any of the above-mentioned methods includes the following steps: S1. Using the composite fiber as the core yarn and the nylon as the outer yarn, a blended yarn is prepared in proportion. The blended yarn is used as the warp and weft yarns, and a woven fabric is prepared by weaving with a warp density of 580~600 threads / 10cm and a weft density of 220~240 threads / 10cm. S2. After dyeing the woven fabric, it is fixed at 165~175℃ to obtain the fixed fabric. S3. The pre-formed fabric is subjected to two padding processes in a photocatalytic hydrosol. During the first padding process, ultraviolet (UV) treatment is performed simultaneously. The temperature of the photocatalytic hydrosol is 25-55°C, the roll-off rate is 65-85%, and the UV power is 500-600mW. During the second padding process, ultrasonic vibration treatment is performed simultaneously. The temperature of the photocatalytic hydrosol is 25-55°C, the roll-off rate is 90-100%, and the ultrasonic vibration frequency is 50-60KHz, thereby obtaining the padded fabric. S4. Dry and set the impregnated fabric at 100~115℃ for 5~10 minutes to obtain the textile fabric.
[0013] Furthermore, the photocatalyst hydrosol is an aqueous solution of nano-titanium dioxide with a concentration of 6~9 mg / L, wherein the particle size of the nano-titanium dioxide is 5~10 nm.
[0014] Note: Nano titanium dioxide has excellent UV absorption and reflection capabilities, which can significantly improve the UV protection function of fabrics and protect the skin from UV radiation damage. Under light conditions, nano titanium dioxide photocatalyst can decompose organic pollutants on the fabric surface, such as oil and dust, to achieve a self-cleaning effect.
[0015] Furthermore, after obtaining the impregnated fabric, electrostatic spraying of self-cleaning powder is performed starting from one side of the impregnated fabric and proceeding towards the other side of the impregnated fabric. The electrostatic spraying method is as follows: First, spray the first layer onto the impregnated fabric. The width of the first layer is 1 / 8 to 1 / 6 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Then, starting from 20 to 30% of the width of the first layer, spray the second layer. Then, starting from 20 to 30% of the width of the second layer, spray the third layer, until the entire impregnated fabric is sprayed. The spraying area of each layer is the same, and after each layer is sprayed, the coated padding fabric is heat-treated at 100~120℃ for 20~30 minutes. In the electrostatic spraying process, the distance between the spray gun and the padding fabric is 200~250mm, the voltage is 60~70kV, the current is 55~65μA, the compressed air pressure is 0.2~0.4MPa, and the spraying thickness is 45~65μm.
[0016] Explanation: The multi-layered overlapping structure provides better protection, reduces wear and tear on the fabric surface caused by friction, and helps to disperse external forces, reducing scratch damage to the fabric. It can also increase the roughness of the fabric surface, helping to capture and remove dust particles, thereby improving self-cleaning ability. Electrostatic spraying technology ensures that the powder adheres firmly to the fabric surface, providing a durable coating. Heat treatment after each layer of spraying helps chemical bonding between the powder coating and the impregnated fabric, thereby enhancing the coating's adhesion and preventing peeling. Heat treatment can eliminate internal stress in the coating and improve its mechanical properties, such as elasticity, toughness, and impact resistance.
[0017] Furthermore, the self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder, and silane coupling agent in a mass ratio of 1:0.4:0.2~0.3.
[0018] Explanation: Tourmaline negative ion powder can release negative ions, which have the ability to adsorb and decompose harmful substances in the air, helping to keep the fabric clean. Polycarbonate powder provides good mechanical properties, while silane coupling agent can improve the bonding force between tourmaline and polycarbonate, improve the overall coating's wear resistance and chemical resistance. As a surface modifier, silane coupling agent can improve the dispersion and adhesion of tourmaline powder in polycarbonate powder, ensuring the stability of the coating.
[0019] Compared with existing composite fiber textiles, the advantages of this invention are: (1) The textile fabric of the present invention is composed of nylon, modified polyester-cotton fiber and island fiber. The high strength and abrasion resistance of nylon and modified polyester-cotton fiber make the fabric more durable and tear-resistant. Even after multiple washes, it can still maintain good antibacterial and self-cleaning properties. The microstructure of island fiber and appropriate textile process can make the fabric have good waterproof and breathable properties, while providing heat insulation and warmth. In addition, island fiber has high abrasion resistance and strength, and can withstand a certain degree of washing and use, maintaining good appearance and performance. Furthermore, island fiber has natural antibacterial properties, which can effectively prevent the growth of bacteria and mold.
[0020] (2) In the process of impregnating the fabric, the textile fabric of the present invention is subjected to a first impregnation combined with ultraviolet treatment. The photocatalyst in the photocatalyst hydrosol can generate highly active free radicals under ultraviolet irradiation, which have strong oxidizing properties and can effectively decompose organic pollutants and bacteria in the air, thereby improving the self-cleaning and antibacterial properties of the fabric. The second impregnation is combined with ultrasonic vibration treatment. Ultrasonic vibration treatment can promote the uniform distribution of photocatalyst hydrosol on the fabric surface, reduce coating defects, improve the uniformity and adhesion of the coating, thereby enhancing the photocatalytic activity and stability of the fabric. Attached Figure Description
[0021] Figure 1 This is a comparison chart of the results of the first investigation into the textile fabric of this invention; Figure 2 This is a comparison chart of the results of the second investigation into the textile fabric of this invention; Figure 3 This is a comparison chart of the results of the third investigation into the textile fabric of this invention; Figure 4 This is a partial view of the electrostatic spraying process of the present invention. Detailed Implementation
[0022] To further illustrate the methods and effects of this invention, the technical solution of this invention will be clearly and completely described below in conjunction with experiments.
[0023] Example 1: A composite fiber textile fabric, comprising the following components by weight percentage: Nylon: 70%; Composite fiber: Balance; The composite fiber is composed of modified polyester-cotton fiber and island fiber in a mass ratio of 1:0.5; The method for preparing the modified polyester-cotton fiber is as follows: Polyester-cotton fibers were immersed in a hydrogel precursor solution at a solid-liquid ratio of 1g:50mL. A vacuum was applied to reduce the pressure to 72kPa. The hydrogel precursor solution was then heated to 90℃ and maintained for 35min. The surface of the polyester-cotton fibers was then subjected to corona treatment at a temperature of 30℃, a voltage of 20kV, and a treatment time of 10min. The distance between the electrodes of the corona treatment device and the polyester-cotton fibers was 2mm. After the corona treatment, the resulting polyester-cotton fibers were immersed in a 15% sodium hydroxide solution at a solid-liquid ratio of 1g:25mL. A vacuum was then applied again to reduce the pressure to 15kPa and maintained for 8min. The polyester-cotton fibers were then removed and dried at 70℃ to obtain modified polyester-cotton fibers. The hydrogel precursor solution comprises, by weight, 18 parts cellulose solution, 8 parts antibacterial agent, 4 parts nano zinc oxide and 9 parts octadecyl mercaptan, wherein the antibacterial agent is a silver ion antibacterial agent and the nano zinc oxide has a particle size of 43-47 nm.
[0024] Example 2: A method for preparing the composite fiber textile fabric as described in Example 1, comprising the following steps: S1. Using the composite fiber as the core yarn and the nylon as the outer yarn, a blended yarn is prepared in proportion. The blended yarn is used as the warp and weft yarns, and a woven fabric is prepared by weaving with a warp density of 590 threads / 10cm and a weft density of 230 threads / 10cm. S2. After dyeing the woven fabric, it is fixed at 170°C to obtain a fixed fabric; wherein, the dyeing is to immerse the woven fabric in a dyeing vat containing PC dye for 45 minutes. S3. The pre-formed fabric is subjected to two padding processes in a photocatalytic hydrosol. During the first padding process, ultraviolet (UV) treatment is performed simultaneously. The temperature of the photocatalytic hydrosol is 40°C, the roll-off rate is 70%, and the UV power is 550mW. During the second padding process, ultrasonic vibration treatment is performed simultaneously. The temperature of the photocatalytic hydrosol is 40°C, the roll-off rate is 95%, and the ultrasonic vibration frequency is 55kHz, resulting in the padded fabric. The photocatalytic hydrosol is a 7.5mg / L aqueous solution of nano-titanium dioxide, wherein the particle size of the nano-titanium dioxide is 6~8nm. S4. Dry and set the impregnated fabric at 112°C for 8 minutes to obtain the textile fabric.
[0025] Example 3: This example differs from Example 1 in that a composite fiber textile fabric, by mass percentage, comprises the following components: Nylon: 60%; Composite fiber: balance; The composite fiber is composed of modified polyester-cotton fiber and island fiber in a mass ratio of 1:0.4.
[0026] Example 4: This example differs from Example 1 in that a composite fiber textile fabric, by mass percentage, comprises the following components: Nylon: 80%; Composite fiber: balance; The composite fiber is composed of modified polyester-cotton fiber and island fiber in a mass ratio of 1:0.6.
[0027] Example 5: The difference between this example and Example 1 is that the polyester-cotton fibers were immersed in the hydrogel precursor solution at a solid-liquid ratio of 1g:40mL, the air pressure was reduced to 70kPa by evacuation, and the hydrogel precursor solution was heated to 85°C and maintained for 30min.
[0028] Example 6: The difference between this example and Example 1 is that the polyester-cotton fibers were immersed in the hydrogel precursor solution at a solid-liquid ratio of 1g:60mL, the air pressure was reduced to 75kPa by evacuation, and the hydrogel precursor solution was heated to 95°C and maintained for 40min.
[0029] Example 7: This example differs from Example 1 in that the irradiation temperature of the corona treatment is 20°C, the voltage is 15kV, the treatment time is 5min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 0.5mm.
[0030] Example 8: This example differs from Example 1 in that the irradiation temperature of the corona treatment is 20°C, the voltage is 25kV, the treatment time is 15min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 4.5mm.
[0031] Example 9: The difference between this example and Example 1 is that the polyester-cotton fibers obtained by corona treatment are immersed in a 10% sodium hydroxide solution at a solid-liquid ratio of 1g:20mL, and the vacuum is continued to reduce the air pressure to 10kPa and maintained for 5min.
[0032] Example 10: The difference between this example and Example 1 is that the polyester-cotton fibers obtained by corona treatment are immersed in a 20% sodium hydroxide solution at a solid-liquid ratio of 1g:30mL, and the vacuum is continued to reduce the air pressure to 20kPa and maintained for 10min.
[0033] Example 11: This example differs from Example 1 in that the hydrogel precursor solution, by weight, comprises: 15 parts cellulose solution, 10 parts antibacterial agent, 5 parts nano zinc oxide, and 10 parts octadecyl mercaptan.
[0034] Example 12: This example differs from Example 1 in that the hydrogel precursor solution, by weight, comprises: 20 parts cellulose solution, 5 parts antibacterial agent, 3 parts nano zinc oxide, and 8 parts octadecyl mercaptan.
[0035] Example 13: The difference between this example and Example 1 is that the antibacterial agent is a silver ion antibacterial agent and the particle size of the nano zinc oxide is 40~43nm.
[0036] Example 14: The difference between this example and Example 1 is that the antibacterial agent is a guanidine antibacterial agent and the particle size of the nano zinc oxide is 47~50nm.
[0037] Example 15: The difference between this example and Example 2 is that the warp density is 580 threads / 10cm and the weft density is 220 threads / 10cm.
[0038] Example 16: The difference between this example and Example 2 is that the warp density is 600 threads / 10cm and the weft density is 240 threads / 10cm.
[0039] Example 17: The difference between this example and Example 2 is that the woven fabric is dyed and then fixed at 165°C to obtain a fixed fabric.
[0040] Example 18: The difference between this example and Example 2 is that the woven fabric is dyed and then fixed at 175°C to obtain a fixed fabric.
[0041] Example 19: The difference between this example and Example 2 is that ultraviolet treatment is performed during the single impregnation process, the temperature of the photocatalyst hydrosol is 25°C, the roll residue is 65%, and the ultraviolet power is 500mW.
[0042] Example 20: This example differs from Example 2 in that it involves combined ultraviolet treatment during a single impregnation process, with the photocatalyst hydrosol temperature at 55°C, the roll residue rate at 85%, and the ultraviolet power at 600mW.
[0043] Example 21: The difference between this example and Example 2 is that ultrasonic vibration treatment is carried out during the second impregnation and rolling, the temperature of the photocatalyst hydrosol is 25°C, the roll residue rate is 90%, and the ultrasonic vibration frequency is 50KHz.
[0044] Example 22: The difference between this example and Example 2 is that ultrasonic vibration treatment is performed during the second impregnation, the temperature of the photocatalyst hydrosol is 55°C, the roll residue rate is 100%, and the ultrasonic vibration frequency is 60KHz.
[0045] Example 23: The difference between this example and Example 2 is that the photocatalytic hydrosol is an aqueous solution of nano-titanium dioxide with a concentration of 6 mg / L, wherein the particle size of the nano-titanium dioxide is 8~10 nm.
[0046] Example 24: The difference between this example and Example 2 is that the photocatalytic hydrosol is an aqueous solution of nano-titanium dioxide with a concentration of 9 mg / L, wherein the particle size of the nano-titanium dioxide is 5~6 nm.
[0047] Example 25: The difference between this example and Example 2 is that the impregnated fabric is dried and set at 100°C for 5 minutes to obtain the textile fabric.
[0048] Example 26: The difference between this example and Example 2 is that the impregnated fabric is dried and set at 115°C for 10 minutes to obtain the textile fabric.
[0049] Example 27: This example differs from Example 2 in that, after obtaining the impregnated fabric, electrostatic spraying of self-cleaning powder is performed starting from one side of the impregnated fabric and proceeding towards the other side of the impregnated fabric. The electrostatic spraying method is as follows: like Figure 4As shown, the spray width of the first layer accounts for 1 / 7 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Then, starting from 25% of the width of the first layer, the second layer is sprayed, and starting from 25% of the width of the second layer, the third layer is sprayed, until the entire impregnated fabric is sprayed. The spraying area of each layer is the same, and after each layer is sprayed, the sprayed padding fabric is heat-treated at 110°C for 25 minutes. In the electrostatic spraying process, the distance between the spray gun and the padding fabric is 225mm, the voltage is 65kV, the current is 60μA, the compressed air pressure is 0.3MPa, and the spraying thickness is 50μm. The self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder, and silane coupling agent in a mass ratio of 1:0.4:0.25.
[0050] Example 28: The difference between this example and Example 27 is that the spray width of the first layer accounts for 1 / 8 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Then, starting from 20% of the width of the first layer, the second layer is sprayed, and starting from 20% of the width of the second layer, the third layer is sprayed, until the entire impregnated fabric is sprayed.
[0051] Example 29: The difference between this example and Example 27 is that the spray width of the first layer accounts for 1 / 6 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Then, starting from 30% of the width of the first layer, the second layer is sprayed, and starting from 30% of the width of the second layer, the third layer is sprayed, until the entire impregnated fabric is sprayed.
[0052] Example 30: The difference between this example and Example 27 is that, after each layer of spraying is completed, the sprayed impregnated fabric is first heat-treated at 100°C for 20 minutes.
[0053] Example 31: The difference between this example and Example 27 is that, after each layer of spraying is completed, the sprayed impregnated fabric is first heat-treated at 120°C for 30 minutes.
[0054] Example 32: The difference between this example and Example 27 is that in the electrostatic spraying, the distance between the spray gun and the padding fabric is 200mm, the voltage is 60kV, the current is 55μA, the compressed air pressure is 0.2MPa, and the spraying thickness is 65μm.
[0055] Example 33: The difference between this example and Example 27 is that in the electrostatic spraying, the distance between the spray gun and the padding fabric is 250mm, the voltage is 70kV, the current is 65μA, the compressed air pressure is 0.4MPa, and the spraying thickness is 45μm.
[0056] Example 34: This example differs from Example 27 in that the self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder, and silane coupling agent in a mass ratio of 1:0.4:0.2.
[0057] Example 35: This example differs from Example 27 in that the self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder, and silane coupling agent in a mass ratio of 1:0.4:0.3.
[0058] Experimental Example: The description of this experimental example is based on the scheme described in Example 2, and aims to illustrate the practical application effect of the present invention.
[0059] To investigate the antibacterial properties and wash fastness of the textile fabric prepared by this invention, tests were conducted in accordance with GB / T20944.3-2008. Staphylococcus aureus was used as the antibacterial test strain to observe its antibacterial activity. The test sample was subjected to 300 standard washes to observe its wash fastness, i.e., its antibacterial activity after washing.
[0060] 1. To investigate the effects of the composition ratio of textile fabrics and the preparation parameters of modified polyester-cotton fibers on the antibacterial rate and wash fastness of textile fabrics.
[0061] The difference between Comparative Example 1 and Example 1 is that no corona treatment was performed; Depend on Figure 1 The results show that the antibacterial rate of Control Example 1, which lacks corona treatment, is significantly lower than that of Examples 1, 3-14. Therefore, corona treatment has a certain effect on improving the antibacterial rate and wash fastness of textile fabrics. Comparing Examples 1 and 3-14, it can be seen that too small or too large a proportion of nylon, too small or too large parameters for immersing polyester / cotton fibers in the hydrogel precursor solution, too small or too large parameters for corona treatment, too small or too large parameters for immersing polyester / cotton fibers in the sodium hydroxide solution, too small or too large a proportion of cellulose solution in the hydrogel precursor, and too small or too large particle size of nano zinc oxide will all reduce the antibacterial rate and wash fastness of the textile fabric. Therefore, in summary, the parameters of Example 1 are relatively better.
[0062] 2. To investigate the effects of the composition ratio of textile fabrics and the preparation parameters of modified polyester-cotton fibers on the antibacterial rate and wash fastness of textile fabrics.
[0063] The difference between Comparative Example 2 and Example 2 is that ultraviolet irradiation was eliminated during the single impregnation process; The difference between Comparative Example 3 and Example 2 is that the ultrasonic vibration treatment was omitted during the second impregnation. Depend on Figure 2The results showed that, compared with Examples 2 and 15-26, the antibacterial rates of Control Example 2, which lacked ultraviolet irradiation, and Control Example 3, which lacked ultrasonic vibration treatment, were significantly lower. Therefore, the combined ultraviolet irradiation and ultrasonic vibration treatment during padding has a certain effect on improving the antibacterial rate and wash fastness of textile fabrics. Comparing Examples 2 and 15-26, it can be seen that excessively low or high warp and weft density, excessively low or high preform parameters, excessively low or high parameters for the first impregnation, excessively low or high parameters for the second impregnation, and excessively low or high parameters for the photocatalytic hydrosol will all reduce the antibacterial rate and wash fastness of the textile fabric. Therefore, in summary, the parameters of Example 2 are relatively better.
[0064] 2. To investigate the effects of the composition ratio of textile fabrics and the preparation parameters of modified polyester-cotton fibers on the antibacterial rate and wash fastness of textile fabrics.
[0065] The difference between Comparative Example 4 and Example 27 is that only one layer of self-cleaning powder is sprayed onto the entire impregnated fabric. Depend on Figure 3 The results show that the antibacterial rate and wash fastness of the textile fabrics in Examples 27-35 are improved compared with those in Example 2. In contrast, the control example 4 lacks the layered structure of self-cleaning powder, and its antibacterial rate and wash fastness of the textile fabrics are reduced compared with Examples 27-35. Therefore, the sprayed layered structure of self-cleaning powder has a certain effect on improving the antibacterial rate and wash fastness of textile fabrics. Comparing Examples 27-35, it can be seen that too small or too large overlapping area, too small heat treatment parameters, too small or too large electrostatic spraying parameters, and too small or too large proportion of tourmaline negative ion powder in self-cleaning powder will reduce the antibacterial rate and wash fastness of textile fabrics. In Example 31, the heat treatment temperature is higher and the treatment time is longer, which improves the performance compared to Example 27, but the improvement is small. Therefore, from an economic point of view, the parameters of Example 27 are relatively better.
Claims
1. A method for preparing a composite fiber textile fabric, characterized in that, Includes the following steps: S1. A blended yarn is prepared by using composite fiber as the core yarn and nylon as the outer yarn in a certain proportion. The blended yarn is then used as the warp and weft yarns and woven into a fabric with a warp density of 580-600 ends / 10cm and a weft density of 220-240 ends / 10cm. The composite fiber includes modified polyester-cotton fiber. The method for preparing the modified polyester-cotton fiber is as follows: Polyester-cotton fibers were immersed in a hydrogel precursor solution at a solid-liquid ratio of 1g:40-60mL. A vacuum was applied to reduce the pressure to 70-75kPa. The hydrogel precursor solution was then heated to 85-95℃ and maintained for 30-40 minutes. The surface of the polyester-cotton fibers was then subjected to corona treatment. The irradiation temperature for the corona treatment was 20-40℃, the voltage was 15-25kV, and the treatment time was 5-15 minutes. The distance between the electrodes of the corona treatment device and the polyester-cotton fibers was 0.5-4.5mm. After the corona treatment, the obtained polyester-cotton fibers were immersed in a 10-20% sodium hydroxide solution at a solid-liquid ratio of 1g:20-30mL. A vacuum was applied again to reduce the pressure to 10-20kPa and maintained for 5-10 minutes. The polyester-cotton fibers were then removed and dried to obtain modified polyester-cotton fibers. The hydrogel precursor solution comprises, by weight, 15-20 parts cellulose solution, 5-10 parts antibacterial agent, 3-5 parts nano zinc oxide and 8-10 parts octadecyl mercaptan. S2. After dyeing the woven fabric, it is fixed at 165~175℃ to obtain the fixed fabric. S3. The pre-formed fabric is subjected to two padding processes in a photocatalytic hydrosol. During the first padding process, ultraviolet (UV) treatment is performed simultaneously. The temperature of the photocatalytic hydrosol is 25-55°C, the roll-off rate is 65-85%, and the UV power is 500-600mW. During the second padding process, ultrasonic vibration treatment is performed simultaneously. The temperature of the photocatalytic hydrosol is 25-55°C, the roll-off rate is 90-100%, and the ultrasonic vibration frequency is 50-60KHz, thereby obtaining the padded fabric. After obtaining the impregnated fabric, electrostatic spraying of self-cleaning powder is performed starting from one side of the impregnated fabric and proceeding towards the other side of the impregnated fabric. The self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder, and silane coupling agent in a mass ratio of 1:0.4:0.2~0.
3. S4. Dry and set the impregnated fabric at 100~115℃ for 5~10 minutes to obtain the textile fabric.
2. The method for preparing a composite fiber textile fabric as described in claim 1, characterized in that, The textile fabric comprises, by weight percentage, the following components: Nylon: 60~80%; Composite fiber: Balance; The composite fiber is composed of modified polyester-cotton fiber and island fiber in a mass ratio of 1:0.4~0.
6.
3. The method for preparing a composite fiber textile fabric as described in claim 1, characterized in that, The antibacterial agent is a silver ion antibacterial agent or a guanidine antibacterial agent, and the particle size of the nano zinc oxide is 40~50nm.
4. The method for preparing a composite fiber textile fabric as described in claim 1, characterized in that, The photocatalyst hydrosol is an aqueous solution of nano-titanium dioxide with a concentration of 6~9 mg / L, wherein the particle size of the nano-titanium dioxide is 5~10 nm.
5. The method for preparing a composite fiber textile fabric as described in claim 1, characterized in that, The electrostatic spraying method is as follows: First, spray the first layer onto the impregnated fabric. The width of the first layer is 1 / 8 to 1 / 6 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Then, starting from 20 to 30% of the width of the first layer, spray the second layer. Then, starting from 20 to 30% of the width of the second layer, spray the third layer, until the entire impregnated fabric is sprayed. Each layer has the same spraying area, and after each layer is sprayed, the coated padding fabric is heat-treated at 100~120℃ for 20~30 minutes. In the electrostatic spraying process, the distance between the spray gun and the padding fabric is 200~250mm, the voltage is 60~70kV, the current is 55~65μA, the compressed air pressure is 0.2~0.4MPa, and the spraying thickness is 45~65μm.
Citation Information
Patent Citations
Antibacterial textile and preparation method thereof
CN107938310A
Preparation method of anti-yellowing silver-containing dressing
CN109276747A